Memediasi Pertumbuhan Ekonomi Dengan Kemiskinan: Studi Kasus Provinsi Daerah Istimewa Yogyakarta - Nur Wani; Suharno Suharno; Arintoko Arintoko (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2020)
The results of empirical studies on the effect of economic growth with poverty show conflicting results. Therefore, this study tries to introduce employment opportunities as a mediating variable. The research objective is to examine whether employment opportunities are able to mediate between economic growth and poverty. The data used in this study are secondary data of DIY Province in the period 2000-2018. The method used in this research is path analysis. The results showed that the three hypotheses above were supported. Thus, economic growth will be able to reduce the number of poor people if the economic growth is able to grow employment opportunities. The finding implies the importance of inclusive growth that gives poor people access to work and business opportunities.